Perception of Elderly People on Old Age Allowance at Dhurkot Rural Municipality in Gulmi - Kunwar, Thaneshwar (RR Interdisciplinary Journal, 2024)
Aging is a gradual, continuous process of natural change that begins in early adulthood. The objective of the study was to analyse the perception of elderly people on old age allowance at Dhurkot Rural Municipality in Gulmi district. Purposively three wards were chosen for sample population. Total elderly people were 930 aged 60 years and above. A total of 280 samples were determined by using Yamene equation, n=N/1+Ne2. Where, n= Sample size, N=Population size, e=margin of error. Finding shows that Hill Chhetri has the strongest effect on “perception of elderly people on old age allowance”. More than nineteen times [OR= 19.33 (2.55-146.34)] Hill Chhetri and three times [OR=2.81(1.39-5.67)] Hill Dalits have said old age allowance is sufficient than elderly belong to Hill Brahmin. Elderly people belonging to other occupation have said that old age allowance is sufficient than elderly whose occupation is agriculture [OR= .25(.1-.59)] which is significant at .01 percent. Elderly people belong to the age of 65-69 years have said that elderly allowance is sufficient than elderly belongs to 60-64 years [OR=.75(.009-.64)]. Elderly belongs to age group of 70-74 years have said that old age allowance is sufficient than elderly belongs to 60-64 years [OR=.16(.021-.1.35)]. Elderly people belong to age group 75 years and above have said that old age allowance is sufficient to fulfil the basic needs than elderly belongs to 60-64 years [OR= .13(.018-1.03)]. Hill elderly people belong to Chhetri and Dalit castes are much satisfied of getting old age allowance than others. Various health schemes, policies and programmes can be designed in the research area and similar settings based on the study findings.